2021
DOI: 10.1021/acsanm.0c03484
|View full text |Cite
|
Sign up to set email alerts
|

Black TiO2–x Nanoparticles Decorated with Ni Nanoparticles and Trace Amounts of Pt Nanoparticles for Photocatalytic Hydrogen Generation

Abstract: A cocatalyst plays an essential role in photoassisted hydrogen generation, and it is an almost inevitable component of a photocatalyst. Costly noble metal (e.g., Pt) cocatalysts exhibit almost irreplaceable efficiencies, and finding a suitable replacement is a challenging proposition. Controlled synthesis of a nanoparticle cocatalyst on semiconductors at the nanoscale level is one of the most promising approaches to accomplish the Pt equivalent activity. Herein, a photodeposited metallic Ni-based cocatalyst co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 68 publications
(114 reference statements)
0
12
0
Order By: Relevance
“…The development of robust photocatalysts for efficient harvesting of broadband solar radiation, particularly near-infrared wavelengths, is essential for the solar-to-fuel technology. Most commonly used semiconductor-based photocatalysts operate in the UV and visible wavelengths. two-dimensional (2D)-nanomaterial-based photocatalysts enhance the charge transfer kinetics and surface activity due to high surface-to-volume ratios, and the light harvesting can be extended; however, it requires a complex preparation process. Organic molecules provide the wavelength flexibility, but they also suffer from acute photobleaching. , Plasmonic nanoparticles have recently emerged as potential photocatalysts for visible as well as near-infrared (NIR) wavelengths due to their tunable plasmon resonance wavelengths across the visible and NIR spectral range. The surface plasmon resonance (SPR) of a plasmonic nanostructure is sensitive toward its size, shape, and the surrounding dielectric environment. , The SPR band of isotropic nanostructures such as gold nanospheres (AuNSs) can be tuned in the range of 500–580 nm, while that of anisotropic nanostructures such as nanorods and nanoprisms is tunable over the entire visible–NIR wavelength ranges, providing an opportunity to harvest photons from the entire visible–NIR region. ,, The photoexcitation of the surface plasmons creates energetic charge carriers, commonly known as hot carriers. These charge carriers can initiate and enhance a chemical reaction on the surface of these nanoparticles. However, the incident photon-to-chemical conversio...…”
Section: Introductionmentioning
confidence: 99%
“…The development of robust photocatalysts for efficient harvesting of broadband solar radiation, particularly near-infrared wavelengths, is essential for the solar-to-fuel technology. Most commonly used semiconductor-based photocatalysts operate in the UV and visible wavelengths. two-dimensional (2D)-nanomaterial-based photocatalysts enhance the charge transfer kinetics and surface activity due to high surface-to-volume ratios, and the light harvesting can be extended; however, it requires a complex preparation process. Organic molecules provide the wavelength flexibility, but they also suffer from acute photobleaching. , Plasmonic nanoparticles have recently emerged as potential photocatalysts for visible as well as near-infrared (NIR) wavelengths due to their tunable plasmon resonance wavelengths across the visible and NIR spectral range. The surface plasmon resonance (SPR) of a plasmonic nanostructure is sensitive toward its size, shape, and the surrounding dielectric environment. , The SPR band of isotropic nanostructures such as gold nanospheres (AuNSs) can be tuned in the range of 500–580 nm, while that of anisotropic nanostructures such as nanorods and nanoprisms is tunable over the entire visible–NIR wavelength ranges, providing an opportunity to harvest photons from the entire visible–NIR region. ,, The photoexcitation of the surface plasmons creates energetic charge carriers, commonly known as hot carriers. These charge carriers can initiate and enhance a chemical reaction on the surface of these nanoparticles. However, the incident photon-to-chemical conversio...…”
Section: Introductionmentioning
confidence: 99%
“…56 The charge transfer of Ni 2+ in the form of Ni(OH) 2 co-catalyst can be regarded as an intermediate process of the reaction, and its role in the catalytic system is secondary. 16 Therefore, the photocatalytic activity of Ni-THS mainly depends on the intrinsic absorption of THS in the ultraviolet region and the weak absorption of visible light by Ni promoters.…”
Section: Possible Photocatalytic Mechanismmentioning
confidence: 99%
“…15 Biswas et al fully ground NaBH 4 and TiO 2 in a crucible, and TiO 2 with oxygen vacancies was successfully synthesized after annealing in a N 2 atmosphere. 16 Compared with other morphologies of TiO 2 , spherical titanium oxide with oxygen defects which exhibited large specific surface area, high efficiency of light utilization and abundant reactive sites has been extensively employed as the photocatalyst. 17,18 For instance, Hu et al used a one-pot solvothermal method to prepare 3D hierarchical TiO 2 spheres rich in oxygen vacancies, through the redox reaction between the electrons captured by the oxygen vacancies and metal ions; the precious metals are uniformly deposited on the spheres, which enhances light absorption and photo-generated charge separation.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have reported that noble metal NPs, such as Au, Pt, Ag, Rh, Ni-Pt, Pd, Cu-Pd, and Au-Pd have been reported resulting in enhanced overall photocatalytic activity by enhancing the electron-hole charge separation. [61][62][63][64][65][66][67][68][69][70][71] In this regard, SnS 2 nanostructures were synthesized by hydrothermal method and were in situ decorated with Ni as a cocatalyst having different concentrations of Ni i.e., 1 mol%, 2.5 mol%, 5 mol%, and 10 mol% through a simple thermal reduction method. The detailed physico-chemical characterisation and inuence of Ni loading on SnS 2 towards its photocatalytic performance were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have reported that noble metal NPs, such as Au, Pt, Ag, Rh, Ni-Pt, Pd, Cu-Pd, and Au-Pd have been reported resulting in enhanced overall photocatalytic activity by enhancing the electron–hole charge separation. 61–71…”
Section: Introductionmentioning
confidence: 99%